Woman with her head on the desk - Thomas Hart Benton (artist):::Creator:::::::::::: (2024)
Illustration of a woman with her head on her desk from The Grapes of Wrath, vol.1 p.106, illustrated edition, by Thomas Hart Benton, a native of eastern Oklahoma, who was assigned to draw archetypal Oklahomans for 20th Century Fox as the studio believed that would make the casting more accurate. Chapter nine tells of the farmers packing to leave their farms. "In the little houses the tenant people sifted their belongings and the the belongings of their fathers and of their grandfathers. Picked over their possessions for the journey to the west. The men were ruthless because the past had been spoiled, but the women knew how the past would cry out to them in the coming days."